2007
DOI: 10.1892/06-302.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feline Interferon-Omega on the Survival Time and Quality of Life of Cats with Feline Infectious Peritonitis

Abstract: No effect of FeIFN-omega on survival time or quality of life could be demonstrated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…Although feline IFN-σ was also reported to inhibit FIPV in vitro (Mochizuki and others 1994), a double-blind study found this treatment to be ineffective (Ritz and others 2007). Immunosuppressants such as glucocorticoids and cyclophosphamide appear to prolong life but ultimately cannot prevent death (Hartmann and Ritz 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although feline IFN-σ was also reported to inhibit FIPV in vitro (Mochizuki and others 1994), a double-blind study found this treatment to be ineffective (Ritz and others 2007). Immunosuppressants such as glucocorticoids and cyclophosphamide appear to prolong life but ultimately cannot prevent death (Hartmann and Ritz 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Effusions have been reported in 60 to 97 per cent of cats with FIP (Hartmann and others 2003, Lutz and others 1986, Ritz and others 2007). A definitive diagnostic test for FIP is not available (Hartmann and others 2003).…”
Section: Approach To Diagnosismentioning
confidence: 99%
“…However, the diagnosis of FIP was not confirmed in these cats and the study was not controlled. A subsequent double-blinded placebo-controlled treatment trial of 37 cats with confirmed FIP showed no therapeutic benefit (Ritz and others 2007). Survival ranged from three to 200 days, with the median survival time being nine days for the treatment group and eight days for the placebo group.…”
Section: Treatmentmentioning
confidence: 99%
“…250 Recently, a new drug tested in three cats with the dry form of FIP demonstrated efficacy in prolonging life and alleviating signs. Recombinant feline interferon-omega (Virbagen Omega, Virbac, Carros, France) had showed some initial promise in a small, uncontrolled clinical trial.…”
Section: Treatmentmentioning
confidence: 99%